Parental Attachment and Fear of Missing Out among Chinese Adolescents: A Moderated Mediation Model. - Wang, Yuhua; Li, Taiping; Peng, Cong; Wu, Huifen (Journal of Child & Family Studies, 2024)
This study explored the effects of parental attachment, self-differentiation, and difficulties in emotion regulation on Chinese adolescents' fear of missing out (FoMO) in 1,355 junior high school students. After demographic variables were controlled, parental attachment was significantly negatively associated with FoMO. Mediation analysis revealed that self-differentiation partially mediated the relationship between parental attachment and FoMO. Moderated mediation analysis further indicated that the direct path of parental attachment on FoMO and the mediating path of self-differentiation are regulated by difficulties in emotion regulation. The current findings highlight the protective role of emotion-regulation ability in reducing FoMO among adolescents. Prevention or intervention programs should consider improving the level of parent–child attachment and self-differentiation of adolescents to reduce FoMO. Highlights: Comprehensively explore the influencing mechanism of parental attachment on adolescents' FoMO in Chinese collectivism culture. The relationships among attachment to parents, self-differentiation, and FoMO were tested among Chinese adolescents. Self-differentiation mediated the relationship between attachment to parents and FoMO. Good emotion-regulation skills significantly reduced FoMO caused by insecure attachments and reduced FoMO overall by increasing self-differentiation.